Erythrokeratodermia variabilis et progressiva: clinical features, molecular insights, and therapeutic perspectives - Medina España, Nayeli Tatiana; Castro Carranza, Martha; Baños Segura, Claudia (International Journal of Research in Medical Sciences, 2025)
Erythrokeratodermia variabilis et progressiva (EKVP) is a rare genodermatosis characterized by transient, erythematous patches and persistent hyperkeratotic plaques with a highly variable clinical presentation. As a disorder predominantly linked to pathogenic variants in GJB3 and GJB4, encoding connexin proteins essential for intercellular communication, EKVP highlights the critical role of gap junction integrity in epidermal homeostasis. This article aims to provide a comprehensive overview of EKVP, focusing on its clinical manifestations, pathophysiological mechanisms, and the role of molecular diagnostics in confirming the diagnosis. Additionally, emerging treatment strategies, including targeted therapies and advances in genetic counseling, are discussed. Enhanced understanding of EKVP’s molecular underpinnings has paved the way for innovative therapeutic approaches, offering new hope for affected individuals.